El efecto de las importaciones en el sector agrícola caso: arroz durante el periodo de 2016 - 2021 (2023)
In the present work it is tried to Analyze the behavior of the imports of the rice during the period of 2016 - 2021 and the impact on the Colombian economy. giving to know what has the greatest impact on the Colombian agricultural sector; the determiners by which national agriculture, even being of high quality and relevant productivity, cost much more than imported products, this is generated by some variables that affect not only to local producers, but also to the final consumer.